The growth mechanisms of graphene directly on sapphire substrates by using the chemical vapor deposition - Lin, Meng-Yu; Su, Chen-Fung; Lee, Si-Chen; Lin, Shih-Yen (My University, 2014)
Uniform and large-area graphene films grown directly on sapphire substrates by using a low-pressure chemical vapor deposition system are demonstrated in this paper. The evolution process and the similar Raman spectra of the samples with different growth durations have confirmed that the continuous graphene film is formed by graphene flakes with similar sizes. The layer-by-layer growth mechanism of this approach is attributed to the preferential graphene deposition on sapphire surfaces. The etching effect of H-2 gas is demonstrated to be advantageous for the larger graphene grain formation. The smooth surface of substrates is also proved to be a key parameter for continuous graphene film formation with better crystalline quality. (C) 2014 AIP Publishing LLC.